Reference intervals of echocardiographic measurements in healthy adult dairy goats - Szaluś-Jordanow, Olga (PLoS One, 2017)
OBJECTIVES: To determine references intervals for echocardiographic measurements in adult dairy goats. ANIMALS: 125 clinically healthy, adult dairy goats aged 2–9 years, belonging to two breeds–Polish Fawn Improved (PFI, n = 64, weight range from 46 to 73, median of 58.5kg) and Polish White Improved (PWI, n = 61, weight range from 48 to 80 kg, median of 67.9kg), closely related to French Alpine and Saanen, respectively. METHODS: Non-invasive transthoracic echocardiography examination was performed in unsedated goats in a standing position. Two-dimensional, M-mode and pulsed wave Doppler measurements were obtained. A non-parametric method was applied for determination of reference intervals. Measurements for the two breeds were compared using an analysis of covariance to control for their body weight. Repeatability was assessed using a between-day coefficient of variation and a coefficient of repeatability. RESULTS: Following reference intervals were determined: aortic diameter in diastole 2.2–3.3, left atrial diameter in systole 2.5–4.3cm cm, the ratio of the left atrial diameter to the aortic diameter 0.96–1.5, right ventricular internal diameter in diastole 0.4–1.7cm, left ventricular internal diameter in systole and diastole 1.8–3.2 and 3.2–5.6 cm, respectively, inter-ventricular septum thickness in systole and diastole 0.7–1.5 and 0.5–1.1cm, respectively, left ventricular posterior-wall in systole and diastole 0.8–1.6 and 0.5–1.2cm, respectively, E-point to septal separation 0.3–0.8cm, left ventricular fractional shortening 28–54%, left ventricular ejection fraction 55–86%, maximum Left and Right Ventricular Outflow Tract velocity 80–140 cm/s and 70–130 cm/s, respectively Left and Right Ventricular Outflow Tract pressure gradient 2.5–8.9mmHg and 1.9–6.5mmHg, respectively. Most of the differences between the two breeds could be attributed to different body weight. CONCLUSIONS: The study provides echocardiographic reference intervals determined on the highest sample of apparently healthy goats so far enrolled.